A glimpse beneath earth's surface: GLobal HYdrogeology MaPS (GLHYMPS) of permeability and porosity. Issue 11 (9th June 2014) - Gleeson, Tom; Moosdorf, Nils; Hartmann, Jens; van Beek, L. P. H.
Abstract The lack of robust, spatially distributed subsurface data is the key obstacle limiting the implementation of complex and realistic groundwater dynamics into global land surface, hydrologic, and climate models. We map and analyze permeability and porosity globally and at high resolution for the first time. The new permeability and porosity maps are based on a recently completed high‐resolution global lithology map that differentiates fine and coarse‐grained sediments and sedimentary rocks, which is important since these have different permeabilities. The average polygon size in the new map is ~100 km2, which is a more than hundredfold increase in resolution compared to the previous map which has an average polygon size of ~14, 000 km2. We also significantly improve the representation in regions of weathered tropical soils and permafrost. The spatially distributed mean global permeability ~10−15 m2 with permafrost or ~10−14 m2 without permafrost. The spatially distributed mean porosity of the globe is 14%. The maps will enable further integration of groundwater dynamics into land surface, hydrologic, and climate models.